Pengaruh Keselamatan dan Kesehatan Kerja terhadap Prestasi Kerja Karyawan : (Studi pada PT PLN Makassar Area Rayon Timur) - Zulfikry Sukarno; Nurlaely Razak; Dahniyar Daud (Al-Buhuts, 2023)
This study aims to determine whether work safety and work performance affect the work performance of employees at PT. State Electricity Company (Persero) Makassar East Rayon Area. This data collection uses primary data obtained from questionnaires using the saturated sample technique, with a sampling of all 40 employees in 2020 used as a sample. The test method in this study uses classical assumption tests including normality heteroskedastisity and multicolonierity. The analysis method uses SPSS 23 software with multiple regression techniques. The results of this study show that occupational safety has a positive and significant effect on employee work performance. This is evidenced by the significance value of 0.048 < 0.05. Occupational health has a positive and significant effect on employee work performance. This is evidenced by a significance value of 0.008 < 0.05. Occupational safety and occupational health together have a positive and significant effect on the Work Performance of PT. PLN (Persero) Makassar East Rayon Area.